Evaluation of Antimalarial Activity of Methanolic Root Extract of A Rich (Myricaceae) Against -Infected Mice - Zemene Demelash Kifle MSc; Getnet Mequanint Adinew MSc; Mestayet Geta Mengistie MSc; Abyot Endale Gurmu MSc; Engidaw Fentahun Enyew MSc; Bahiru Tenaw Goshu MSc; Gedefaw Getenet Amare MSc (SAGE Publishing, 2020)
Background. The management and control of malaria has become gradually challenging due to the spread of drug-resistant parasites, lack of effective vaccine, and the resistance of vector to insecticides. Consequently, novel agents are urgently needed from different sources including from medicinal plants. In Ethiopia and Uganda, Myrica salicifolia root is traditionally claimed for the treatment of malaria. The aim of this study was to evaluate the in vivo antimalarial activity of root crude extract of M salicifolia . Methods. The parasite, Plasmodium berghei was used in this study since it is an appropriate parasite that is most commonly used because of its higher accessibility. A 4-day suppressive test was employed to evaluate the antimalarial effect of crude extract against early infection. The curative and prophylactic effect of the crude extract was further tested by Rane's test and residual infection procedure. Parasitemia, survival time, packed cell volume, body weight, and rectal temperature of mice were used as evaluation parameters. Windows SPSS version 24 was used to analyze the data and analysis of variance followed by Tukey's honestly significant difference to compare results between groups. Results. The root crude extract of M salicifolia significantly ( P < .05-.0001) suppressed parasitemia. The crude extract exhibited a chemosuppression of 40.90. Conclusion. The development of new antimalarial agents and the finding supports the traditional claims and previous in vitro studies.